PENINGKATAN AKTIVITAS BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI KR3 SMK NEGERI 3 YOGYAKARTA MELALUI PEMBELAJARAN KOOPERATIF TWO STAY TWO STRAY - Arga Daniati (Universitas Negeri Yogyakarta, 2019)
Based on the low participation of the student during the classroom activities, this study aimed to improve students’ participation and academic achievement on Mathematics. The procedures of this study consisted of planning, implementation, observation, and reflection. There were 24 students of Class XI KR 3 SMK N 3 Yogyakarta 2013/2014 participated in this study. Data were obtained through observation sheets, student worksheets, test, and notes. This study implemented a Cooperative learning model action at Two Stay Two Stray. The students were divided into 6 groups (each group consisted 4 students). The results revealed that (1) the students who actively participated in the classroom activities are 77.08%; (2) the students who passed the test 77.35%, and (3) the students who passed the minimum criteria for the study are 87.5%. It can be concluded that implementing Cooperative Learning, Two Stay Two Stray model, is effective to enhance students’ participation and academic achievement in mathematics.